Genetic Diversity and Demographic History of Wax Moths, Galleria mellonella Linnaeus, 1758 and Achroia grisella Fabricius, 1794 (Lepidoptera: Pyralidae) - Sopaladawan , Piyamas Nanork (Trends in Sciences, 2024)
Wax moths, Galleria mellonella Linnaeus, 1758 and Achroia grisella Fabricius, 1794 are the key pests of honeybee colonies worldwide. They cause wax comb damages which lead to colony perishing and absconding. To control these pests, their genetic background and evolution should be considered. In this study, genetic diversity and demographic history of 2 species of wax moth were explored based on mitochondrial genes (COI). Wax moths were collected from northeatern part of Thailand for morphological and DNA analyses. G. mellonella and A. grisella sequences from GenBank were included for genetic diversity and demographic history analyses (total of 80 and 26 sequences, respectively). Overall genetic diversity for A. grisella samples from Northeastern Thailand was relatively low (h = 0.467 ± 0.132 and π = 0.00150 ± 0.00042). Likewise, low genetic diversity was also observed in G. mellonella samples (h = 0.280 ± 0.101 and π = 0.00046 ± 0.00017). Among samples from different global regions, the haplotype and nucleotide diversity of A. grisella were 0.834 ± 0.050 and 0.00996 ± 0.00124, respectively. The haplotype and nucleotide diversity of G. mellonella were 0.709 ± 0.034 and 0.01084 ± 0.00279, respectively. The ML tree revealed that these 2 species were separated into 2 major clades (G. mellonella clade and A. grisella clade). All sequences corresponding to G. mellonella formed to a single monophyletic clade, while all the sequences corresponding to A. grisella formed another single monophyletic clade. Clade G. mellonella was divided into 4 subclades designated as Clade Gm1, Gm2, Gm3 and Gm4, whereas A. grisella clade was divided into 3 subclades designated as Clade Ag1, Ag2 and Ag3. The sum of squares deviation (SSD) and Harpending’s raggedness index (rg) and the results of Tajima’s D and Fu’s Fs tests indicated population expansion was not found in either species. HIGHLIGHTS This study highlighted the genetic diversity of wax moths Galleria mellonella Linnaeus, 1758 and Achroia grisella Fabricius, 1794 in Thailand and other parts of the world. Population expansion was not observed in either species. The results will be useful to predict directions of population distribution of wax moths under certain factors. GRAPHICAL ABSTRACT